2017
DOI: 10.1007/s10103-017-2282-y
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Er:YAG laser assisting topical betamethasone solution in combination with NB-UVB for resistant non-segmental vitiligo

Abstract: Resistant non-segmental vitiligo is difficult to be treated. Ablative erbium-YAG (Er:YAG) laser has been used in the treatment of vitiligo, but the ablation of entire epidermis frustrated the compliance of patients. The purpose of this study is to investigate the effects of fractional Er:YAG laser followed by topical betamethasone and narrow band ultraviolet B (NB-UVB) therapy in the treatment of resistant nonsegmental vitiligo. The vitiligo lesions of each enrolled patient were divided into four treatment par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…At first, we used a Fraxel Herbium laser (Valseriana® Herbium laser) with a wavelength of 1540 nm and high energy level of 1800 mJ/P. We performed only one laser passage for each lesion to achieve micro-areas of epidermal ablation [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…At first, we used a Fraxel Herbium laser (Valseriana® Herbium laser) with a wavelength of 1540 nm and high energy level of 1800 mJ/P. We performed only one laser passage for each lesion to achieve micro-areas of epidermal ablation [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that treatment for three months might be sufficient for induction therapy; however, continuing the treatment for another three months was suggested to preserve of response. In addition, they postulated that ER: YAG may have slower efficacy compared to CO 2 laser due to less photothermal effects; however, it has higher safety profile due to precise ablation of skin compared to CO 2 laser 40 . Similarly, another RCT demonstrated significant effective RR with triple therapy of fractional ER: YAG laser with TCS and NB‐UVB compared to NB‐UVB and TCS.…”
Section: Resultsmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35][36][37][38] Combined fractional ablative lasers with other medical modalities are preferable to conventional lasers due to favorable safety profile and outcome. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] ***Fractional Er:YAG usually have slower response rate with higher safety profile compared to fractional CO 2 laser. [39][40][41][42] Combination of fractional ARLs with topical therapies (including TCS, TCI, and especially 5-FU) with or without UVB therapy (NBUVB or MEL/EL) is recommended in glabrous skin or areas with sparse hairs including distal of toes and fingers, periungual, ankle, and bony prominence areas.…”
Section: Combination Of Nafl With Other Medical Treatment Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They divided four parts such as one of them is control group given NUVB and other three of them took different frequency of energy to calibrate most effective and least painful method of these modality. They found better response at the medium or high energy protocols [41]. Mohtari et al tried to find a unresponsiveness vitiligo part a new modality that is firstly used ER:YAG laser than applied clobetasol or 5-FU dressing and found better cosmetic results via ablation [42].…”
Section: Erbium Laser For Ablation Modalitiesmentioning
confidence: 99%